Defect-Mediated Mechanics in Non-Stoichiometric Oxide Films. (10th January 2018) - Swallow, Jessica G.; Youssef, Mostafa; Van Vliet, Krystyn J.
ABSTRACT: Chemomechanical coupling is a hallmark of the functional oxides that are used widely for energy conversion and storage applications including solid oxide fuel cells (SOFCs). These oxides rely on the presence of oxygen vacancies to enable important properties including ionic conductivity and gas exchange reactivity. However, such defects can also facilitate chemical expansion, or coupling between material volume and defect content. Such chemomechanical coupling is particularly relevant with the recent interest in thin film SOFCs which have the potential to decrease operating temperatures and enable portable applications. Thin films present a particular challenge for modelling, as experimental results indicate that film defect chemistry can differ significantly from bulk counterparts under the same experimental conditions. In this study, we explore the influence of point defects, including oxygen vacancies and cation dopants, on the elastic properties of a model material, Prx Ce1-x O2-δ (PCO), using density functional theory (DFT + U) simulations. Previously, we showed that PCO films exhibit a decrease in Young's elastic modulus E due to chemical expansion, but that this decrease can be larger than predicted based on bulk defect models. Here, we apply DFT + U to show that the biaxial elastic modulus of PCO decreases with increased oxygen vacancy content in both bulk and membrane forms. We consider the relative influences of oxygen vacancies and cation dopants on this trend, and highlight local structural changes in the presence of such defects. By relating our computational and experimental results, we evaluate the relative importance of increased oxygen vacancy content and finite thickness on the mechanical properties of oxides that are subject to chemical expansion under operando conditions. This work informs the design of μ-SOFCs, emphasizing the need to characterize thin films separately from bulk counterparts and demonstrating how functional defect content can influence development of stress and strain in devices by changing both material volume and elastic properties.